(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
In this thesis, the scientific research consists of studying the concepts of man and society in Uzbek and English literature, that is, in the works of Ulugbek Hamdam and Somerset Maugham, their comparative analysis and finding their uniqueness will be briefly covered. The scientific novelty of the research conducted on these works is that the similar and different aspects of the concept of interaction between man and society in Uzbek and English literature were carried out on the basis of a comparative analysis. In the works of writers, the specific characteristics of the ideas of "man and society", the causes and consequences of the problems in mutual relations, the influence of these complications on the human psyche, and the role of this work in the analysis of the artistic light have been studied.